2002
DOI: 10.1177/0032885502238680
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Literature on Prisoners who are Older: Are we Wiser?

Abstract: This article critically reviews the scholarly literature that describes older U.S. inmates and that examines correctional responses to this subpopulation of incarcerated offenders. This review indicates that the number of incarcerated men and women who are older is increasing. Older offenders are primarily incarcerated for violent offenses, and many report one or more chronic health conditions. Health care management is the most prevalent theme in the current literature, and there is tremendous variation in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Although investigators have reported that older male inmates live with an average of three or more chronic or life-threatening illnesses (Krebs, 2000;Loeb & AbuDagga, 2006;Mumola, 2007), those representing ethnic minority groups (e.g., African American, Hispanic American, American Indian) experience fewer chronic health conditions than their White counterparts (Mumola, 2007). It is important to note that most co-occurring health problems among male inmates typically arise from a lifetime of engagement in risky lifestyle behaviors (e.g., smoking, drug abuse, sexual promiscuity) before incarceration (Lemieux, Dyeson, & Castiglione, 2002;Loeb & AbuDagga, 2006;Mumola, 2007). Correctional medical services offer immediate treatment for injury, infectious disease, and chronic illness (Maruschak & Beck, 2001).…”
Section: Health and Older Male Inmatesmentioning
confidence: 99%
“…Although investigators have reported that older male inmates live with an average of three or more chronic or life-threatening illnesses (Krebs, 2000;Loeb & AbuDagga, 2006;Mumola, 2007), those representing ethnic minority groups (e.g., African American, Hispanic American, American Indian) experience fewer chronic health conditions than their White counterparts (Mumola, 2007). It is important to note that most co-occurring health problems among male inmates typically arise from a lifetime of engagement in risky lifestyle behaviors (e.g., smoking, drug abuse, sexual promiscuity) before incarceration (Lemieux, Dyeson, & Castiglione, 2002;Loeb & AbuDagga, 2006;Mumola, 2007). Correctional medical services offer immediate treatment for injury, infectious disease, and chronic illness (Maruschak & Beck, 2001).…”
Section: Health and Older Male Inmatesmentioning
confidence: 99%
“…The United States criminal justice system is undergoing a demographic change in its inmate population, resulting in a rapid increase in the number of older individuals released from its prisons and jails (Neeley, 1997; Lemieus & Dyeson, & Castiglione, 2002; Aday, 2003; Williams, Goodwin, Baillargeon, & Ahalt, 2012). The term “older” has a different meaning in the criminal justice system than it does in general society.…”
Section: Introductionmentioning
confidence: 99%
“…There are now 124,900 prisoners aged 55 and older behind bars compared with just 8,853 in 1981 with projections estimating more than 400,000 by 2030 (American Civil Liberties Union [ACLU], 2012). The changing age structure of the prison population suggests a new urgency to understand the specific health care needs of older prisoners (Lemieux, Dyeson, & Castiglione, 2002; Linder & Meyers, 2007; Reimer, 2008). A recent ACLU (2012) report finds that US$16 billion is spent annually on prisoners aged 50 years and older due largely to high health care expenditures.…”
mentioning
confidence: 99%